Structured object-oriented formal language and method : 7th International Workshop, SOFL+MSVL 2017, Xi'an, China, November 16, 2017, Revised Selected Papers /: 7th International Workshop, SOFL+MSVL 2017, Xi'an, China, November 16, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available